Hubungan Tingkat Pemanfaatan Kawasan Taman Wisata Alam Gunung Kelam Dengan Mata Pencaharian Masyarakat Di Desa Kebong Kecamatan Kelam Permai - Anggi, Anggi Puspita Sari Maman; Suherdiyanto, Suherdiyanto; Sariani, Novita (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study was conducted to examine the relationship between the level of utilization of the Gunung Kelam Nature Tourism Park and the livelihoods of the local community in Kebong Village, Kelam Permai District, Sintang Regency. The study employed a quantitative approach using a correlational research method. A total of 40 respondents were selected through a purposive sampling technique. Data were collected using a questionnaire that had been tested for validity and reliability. The collected data were then analyzed using descriptive statistics, normality testing, linearity testing, and the Pearson Product Moment correlation test. The findings revealed that the average score for the level of utilization of the Gunung Kelam Nature Tourism Park was 65.22, while the average score for community livelihoods was 66.45. Both variables were classified as being in the good category. The correlation analysis produced a correlation coefficient of 0.255 with a significance value of 0.113 (p > 0.05), indicating a positive relationship with a low degree of correlation; however, the relationship was not statistically significant. Therefore, it can be concluded that the level of utilization of the Gunung Kelam Nature Tourism Park has not shown a significant relationship with the livelihoods of the community in Kebong Village, Kelam Permai District, Sintang Regency. The findings of this study are expected to provide useful input for local governments, tourism area managers, and the community in formulating policies and strategies for the sustainable utilization of tourism potential to improve community welfare. Keywords: utilization level, nature tourism park, livelihoods, community, Gunung Kelam Nature Tourism Park, correlational study.